SYSTEMTIS LITERATURE REVIEW : ANALISIS FAKTOR NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT - KHALISHAH, KHANSA; Girsang , Meylida; Sitanggang, Ignatius (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The rupiah exchange rate against the US dollar is significant to study because the dollar exchange rate impacts the global economy. This study aims to provide comprehensive insights and a strong knowledge base for practitioners, academics, and other stakeholders. The method used in this study is SLR (systematic literature review), which will dig deeper by observing, examining, evaluating, and interpreting research using data taken from Google Scholar and Sinta literacy. The study's results indicate that the factors influencing changes in the rupiah exchange rate against the dollar are inflation, money supply, and interest rates.